Most Daunting Aspect of Being a House Officer: A Survey Among Medical Graduates in a Malaysian Public University - Rashid, Aneesa Abdul; Ghazali, Sazlina Shariff; Mohtaruddin, Norhafizah; Hafiz Bin Wan Zukiman, Wan Zul Haikal; Kamal, Farina Mustaffa; Nasharuddin, Nurul Amelina (International Journal of Human and Health Sciences (IJHHS), 2023)
Objectives: Medical graduates often express their unreadiness to work due to several factors. It is important for medical educators to take steps toward assisting house officers (HO) to become work ready. This study assessed the most daunting aspects of being a HO as perceived by medical graduates in a public Malaysian university. Methods: This was part of a larger study entitled “Development of an Online Module for Medical Graduates’ Readiness to Work”. The first part of this study involves an online survey on medical graduates from Universiti Putra Malaysia (UPM) from November 2020 to January 2022. The survey used was the “Confidence and Readiness to Work as a House Officer Questionnaire” that consists of 75 questions altogether. Two of the questions were on readiness to work, of which one asked “In my opinion, the most daunting aspect of being a HO is?” There were 8 choices: (i) Physical demand: difficulty in maintaining patience; (ii) Physical demand: difficulty in maintaining clinical judgement; (iii) Confronting the seniors; (iv) Handling patients with responsibilities (including communication) (v) Competence required in knowledge and judgement; (vi) Competence required in practical skills; (vii) Time management; (viii) Having to adjust to different routines in work and life. Ethics was granted from the Ethics Committee for Research Involving Human Subjects UPM (JKEUPM-2020-341). Results: One hundred and fifty-nine medical graduates completed the questionnaire. They were mostly female (69.2%), single (99.4%), Muslim (56.6%) and Malay (54.7%). The most daunting aspects were “Competence required in knowledge and judgement” (36.5%), followed by “Handling patients with responsibilities (including communication) (17.6%) and “Physical demand: difficulty in maintaining clinical judgement” (15.7%). Conclusion: More than one third of the respondents selected “competence in knowledge and judgement” as the most daunting aspect of becoming HO. Future research should further investigate these factors. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S27